Toxoplasmosis in Relation to Entameba Histolytica and Giardia Lamblia Infection - Al-khushali, Mahmoud N (Diyala Journal of Medicine, 2019)
This study was carried out in Baghdad , on 150 individuals (82 females, 68 males ) , were divided into four groups on the bases of parasitological and serological findings : group I : Control healthy Individuals : negative for toxoplasmosis and E . histolytica and G. lamblia ( 20, 13.3% )group II : positive for toxoplasmosis alone (30 , 20%), group III: positive forE histolytica ,and G. lamblia (63 , 42%), group IV: positive for toxoplasmosis , E . histolytica and G . lamblia ( Mixed infection 37 , 24.7% ). The results of this study showed highly significant increase in serum levels of interleukin -12 ( IL- 12 ) in all groups especially in group IV , followed by group II .The serum level of Interferon –gamma ( IFN- g ) showed also significant increase(P <0.05)in group IV, followed by group III , but nonsignificant (P >0.05) in group II . There was also significant increase in serum concentration of IgG , IgM,and IgE in group IV , but nonsignificant level was recorded in IgE of group II . When comparing group II with the group IV , there was significant difference in serum levels of IL-12 , IFN-g , IgG , IgM and IgE . It was concluded that mixed infection with these parasites could provide a strong synergestic action to induce both cell mediated and humoral immunity .